STRUCTURE AND COOPERATION IN ONLINE COLLABORATION - Sayogo, Djoko Sigit (Faculty of Economics and Business, University of Muhammadiyah Malang, 2011)
Different network configuration influences users’ motivation in collaborating online. While dense and strong ties network induced trust and close collaboration, it restrict expansion. On the other hand, sparse and weak ties stimulate expansion but less trusted collaboration. In addition, there are three instances that would encourage collaboration online. First, certain types of threat exist in online collaboration in the forms of losing reputation, structural position, and censorship. Second, communication augment credibility of threat by accentuating the consequences of threat and reminding of group desired consensus. Finally, online configuration creates ‘sense of community’ that deters deviation.